2007
DOI: 10.1037/0096-1523.33.5.1177
|View full text |Cite
|
Sign up to set email alerts
|

Incidental learning of S-R contingencies in the masked prime task.

Abstract: Subliminal motor priming effects in the masked prime paradigm can only be obtained when primes are part of the task set. In 2 experiments, the authors investigated whether the relevant task set feature needs to be explicitly instructed or could be extracted automatically in an incidental learning paradigm. Primes and targets were symmetrical arrows, with target color, not shape, the response-relevant feature. Shape and color covaried for targets (e.g., ϽϾ always blue, ϾϽ always green), whereas primes were alwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Potentially, with practice, cues might acquire the capability to automatically activate responses (cf. Mordkoff and Halterman, 2008;Schlaghecken et al, 2007), while their influence on expectation might diminish (cf. Gaschler and Nattkemper, 2012).…”
Section: Summarizing the Paths On Which Cues And Self-generated Expecmentioning
confidence: 98%
“…Potentially, with practice, cues might acquire the capability to automatically activate responses (cf. Mordkoff and Halterman, 2008;Schlaghecken et al, 2007), while their influence on expectation might diminish (cf. Gaschler and Nattkemper, 2012).…”
Section: Summarizing the Paths On Which Cues And Self-generated Expecmentioning
confidence: 98%
“…As long as appropriate stimuli are used (see Schlaghecken et al., 2007; Lleras and Enns, 2004; Sumner, 2008), this NCE can be interpreted as reflecting automatic suppression of the primed response (see e.g., Eimer and Schlaghecken, 2003; Jáskowski, 2007, 2008, 2009; Sumner, 2007). According to these sensorimotor accounts of the NCE, initial motor activation evoked by the prime is subsequently suppressed when the prime is removed or a novel stimulus (the mask) is added to the scene (e.g., Boy et al., 2008; Jáskowski, 2007, 2008, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…With more arbitrary S-R mappings, and even sometimes with arrows, there is some indication from previous research that practice can be required to obtain a robust NCE (Klapp & Hinkley, 2002; Sumner, 2008). It has also been found that an NCE can develop gradually for incidental learning of S-R contingencies (Schlaghecken, Blagrove, & Maylor, 2007). In this study participants were instructed to respond to colour, but there was also a consistent relationship between the colour and the shape of the targets.…”
Section: Introductionmentioning
confidence: 99%